The effects of banana stem (musa paradisiaca var. Sapientum) extract on histopathologic gastric of rats induced by indometachin - Kurnijasanti, Rochmah; Putri, Arninda Alfiani (Folia Medica Indonesiana, 2017)
This research aims to find out the administration effect of Ambon banana stem extract (Musa paradisiaca var. sapientum) to prevent gastric damage and observe histopathology of rat's gastric induced by indomethacin. This research used 30 male rats age 8-12 week having 150 gram weight. They were selected randomly and divided into five groups. Negative control (K-) was given 0.5 ml CMC Na 0.5 % for 9 days and 0.5 ml corn oil was given on 10th. Positive control (K+) was given 0.5 ml CMC Na 0.5% for 9 days and then given Indomethacin emultion 5 mg/0.5 ml/150 g BW once on 10th day, and the other groups were given Ambon banana stem extract for (P1) 20 mg/150 g BW, (P2) 40 mg/150 g BW and (P3) 80 mg/150 g BW for 9 days. Afterwards, they were given Indometachin emultion 5 mg/150 g BW once on 10th day. Each gastric specimen was processed and histopathological changes were observed. Scoring of mucosa epithelium erosion and hemorrhagic, as qualitative data, was analyzed by Kruskall-Wallis test and continued by using Z test. The result shows that Pisang Ambon's stem extract reduce significantly in gastric mucosa epithelium erosion and hemorrhagic induced by Indomethacin (p<0.05).